Distance between tumor and nipple as a prognostic factor in breast cancers: Opposite effects in young and old patients. Issue 32 (7th August 2020) - Yang, Qianru; Yang, Jiqiao; Xu, Li; Zhou, Chen; Lv, Qing
Abstract : Abstract: The present study aimed to investigate the prognostic implication of distance from tumor to nipple according to clinicopathological factors with known prognostic value. We retrospectively identified 961 patients of invasive breast cancer from January 2000 to April 2016. Clinicopathological information was extracted from hospital database and distance from tumor to nipple was objectively measured during surgeries. Overall survival (OS) and disease-free survival (DFS) were compared among patients with tumor-nipple distance ⩽2, 2 to 5, and >5 cm. Subgroup analyses were performed according to age at diagnosis (⩽35 vs >35), tumor size, histological features, treatment, axillary nodal metastasis and lymphovascular invasion. A total of 627 cases were included in statistical analysis. There was no difference detected in OS or DFS among patients with different tumor-nipple distance. Better OS was associated with greater tumor-nipple distance in old patients (HR = 0.582, 95%CI: 0.345–0.982, P  = 0.042), while the association between OS and tumor-nipple distance was not observed in young patients. DFS was influenced by tumor-nipple distance in both young (HR = 5.321, 95%CI: 1.151–24.595, P  = 0.032) and old (HR = 0.593, 95%CI: 0.385–0.913, P  = 0.018) patients with opposite effects. Tumor-nipple distance can be adopted as a prognostic factor of breast cancer and it functions oppositely in young and old patients. Multicenter prospective studies with larger sample size are needed to validate the result.